2018
DOI: 10.4103/ejd.ejd_272_17
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of measuring bone density of mandibular condyle in patients at risk of osteoporosis: A cone beam computed tomography study

Abstract: Objective:Using cone beam computed tomography (CBCT) images, the aim of the study was to evaluate the usefulness of measuring bone density of mandibular condyle (BDMC) in patients at risk of osteoporosis.Materials and Methods:Two hundred and four mandibular condyles (46 condyles from males and 158 condyles from females) were examined by CBCT. Using inVivo software (Anatomage, San Jose, Calif), BDMC and mental index (MI) were measured by two observers and correlated using Pearson's correlation coefficients. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…However, few studies were performed on medical doctors' awareness of MRONJ, and how well they refer their patients to dentists. 17 Researchers found that MRONJ is a predictable disease, 18,19 so it is widely accepted that prevention is the best measure of MRONJ treatment. 20 The duration of drugs-dependent therapy and the route of their administration are important risk factors that physicians should take care of to prevent ONJ.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies were performed on medical doctors' awareness of MRONJ, and how well they refer their patients to dentists. 17 Researchers found that MRONJ is a predictable disease, 18,19 so it is widely accepted that prevention is the best measure of MRONJ treatment. 20 The duration of drugs-dependent therapy and the route of their administration are important risk factors that physicians should take care of to prevent ONJ.…”
Section: Discussionmentioning
confidence: 99%
“…The on-demand software (OnDemand 3D APP-DBM, Cybermed, Seoul, South Korea) was used to calculate bone mineral density in Hounsfield Units (HU). Six measurements were taken along the fracture line, and the mean was measured for each patient (17,18).…”
Section: Follow Up Phasementioning
confidence: 99%
“… 20 21 Few up-to-date studies have assessed CBCT indices and they have indicated the possibility of osteoporosis screening based on this imaging modality. 22 23 24 25 Only 2 recent studies have tested FD analysis on CBCT for identifying postmenopausal women with osteoporosis, and those studies reported discordant results. 26 27 Nevertheless, these studies were substantially different in terms of methodology, had small samples, and were only observational, which means that accuracy measurements were not established for the FD method.…”
Section: Introductionmentioning
confidence: 99%